Vibration of viscoelastic sessile droplets - Bennett, Joe (2018)
The surface of viscoelastic polymer solution droplets supported on substrates (sessile droplets) were excited through the application of an impulse supplied by mechanical oscillation of the surface upon which the sessile droplet was resting. The oscillations of these sessile droplets were filmed using a high-speed camera, and the footage was analysed to determine the waveform of the surface waves on the sessile droplets. This waveform was then Fourier transformed to give the vibrational spectra of the surface waves. These spectra were then used to compute the frequency dependent storage modulus (G′) and loss modulus (G″) of the polymer solution. This was done by treating the droplet as a liquid bath with a width defined by the wave vector of the surface waves, and a depth defined by the average height of the droplet. A theoretical model for viscoelastic waves in a liquid bath of finite depth was then used to calculate a theoretical power spectrum which corresponded to the experimental data, which in turn would produce values for the storage and loss moduli. Finally, the contact angle dependence of the vibrational response of the sessile droplets was analysed in order to determine how the geometry of the sessile droplets effects the results of the experiment.